2008
DOI: 10.2527/jas.2008-1085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implants of trenbolone acetate, estradiol, or both, on muscle insulin-like growth factor-I, insulin-like growth factor-I receptor, estrogen receptor-α, and androgen receptor messenger ribonucleic acid levels in feedlot steers1

Abstract: We previously showed that a combined trenbolone acetate (TBA)/estradiol-17beta (E2) implant significantly increases IGF-I mRNA levels in the LM of feedlot steers by 28 d after implantation. Here we compare the effects of E2 (25.7 mg), TBA (120 mg), and combined TBA (120 mg)/E2 (24 mg) implants on IGF-I, IGF-I receptor (IGFR-1), estrogen receptor (ER)-alpha and androgen receptor (AR) mRNA levels in the LM of steers. Twenty yearling crossbred steers with an average initial BW of 421.1 +/- 3.6 kg were stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…However, we elected to measure circulating IGF-I as an indirect positive marker of responses of cattle to growth-promoting steroid implants (Johnson et al, 1996b;Johnson et al, 1998). Additionally, it has been previously shown that implants containing E2 or T+E have a greater ability to stimulate circulating IGF-I than implants containing only TBA (Pampusch et al, 2008). Indeed, our results show a similar finding, and may indicate a greater capability for E2 to affect serum IGF-I concentrations.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, we elected to measure circulating IGF-I as an indirect positive marker of responses of cattle to growth-promoting steroid implants (Johnson et al, 1996b;Johnson et al, 1998). Additionally, it has been previously shown that implants containing E2 or T+E have a greater ability to stimulate circulating IGF-I than implants containing only TBA (Pampusch et al, 2008). Indeed, our results show a similar finding, and may indicate a greater capability for E2 to affect serum IGF-I concentrations.…”
Section: Discussionsupporting
confidence: 72%
“…It has been well documented that steroid growth promotant implants have positive effects on the efficiency and growth of livestock animals, and much is known about the cellular mechanisms behind the changes in muscle (Foutz et al, 1997;Johnson et al, 1998;Barton-Davis et al, 1999;Pampusch et al, 2008). However, there is no current literature on the impacts of steroid implantation on the cellular level of bone growth and resorption that are linked to the steroid-induced increases in bone maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Binding proteins specific for growth hormone and some, although not all, for IGF-I increase in plasma in response to elevated nutrient availability independent of treatment with exogenous growth hormone [37], and the same study indicated that elevated nutrient status actually reduced growth hormone in plasma. Concentration of IGF-I mRNA is elevated in longissimus muscle cells from animals previously administered exogenous E 2 [38,39], and muscle mRNA concentrations for the adipogenic regulators PPARγ and stearoyl CoA desaturase are reduced after administration of exogenous TBA [24]. In addition, both E 2 and TBA, which were used in combination in the present study, stimulate protein synthesis and reduce protein degradation in a dose-dependent manner when directly applied to fused satellite cell cultures [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanisms involved in anabolic steroid stimulated muscle growth in beef cattle are not known with certainty, recent studies indicate that their effects on muscle satellite cells may play a prominent role (Johnson et al, 1998a;Kamanga-Sollo et al, 2008bPampusch et al, 2008). Treatment of yearling steers with Revalor-S (Merck Animal Health, Summit, NJ), an implant containing 120 mg of trenbolone acetate (TBA) and 24 mg of estradiol 17β (E2), significantly increases ADG, feed efficiency, LM area, and carcass protein (Johnson et al, 1998a).…”
Section: Effect Of a Combined Estradiol/trenbo-lone Acetate Implant Omentioning
confidence: 99%